2014
DOI: 10.1016/j.contraception.2014.06.038
|View full text |Cite
|
Sign up to set email alerts
|

Obstetrician-gynecologists’ beliefs on the importance of pelvic examinations in assessing hormonal contraception eligibility

Abstract: Objective: To describe obstetrician-gynecologists' beliefs regarding the importance of pelvic examination (including external genitalia inspection, speculum examination, bimanual examination) in assessing hormonal contraception eligibility. Methods: In a national probability survey, 1020 obstetrician-gynecologists drawn from the American Medical Association's Physician Masterfile rated importance of the examination in four categories: very, moderately, a little and not important. Results: The response rate was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…5 Women and teens experience multiple barriers when accessing and using birth control including prohibitive method costs, limited or nonexistent information about all methods available, and provider bias or outdated clinical practice regarding appropriate candidates for particular contraceptive methods. [6][7][8][9][10] The Contraceptive CHOICE Project was launched to promote the use of long-acting, reversible contraception to reduce the number of unintended pregnancies in the St. Louis region. The project removed three key barriers to use of LARC methods: cost, education, and access.…”
Section: Introductionmentioning
confidence: 99%
“…5 Women and teens experience multiple barriers when accessing and using birth control including prohibitive method costs, limited or nonexistent information about all methods available, and provider bias or outdated clinical practice regarding appropriate candidates for particular contraceptive methods. [6][7][8][9][10] The Contraceptive CHOICE Project was launched to promote the use of long-acting, reversible contraception to reduce the number of unintended pregnancies in the St. Louis region. The project removed three key barriers to use of LARC methods: cost, education, and access.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the notion linking access to hormonal contraception (other than an IUD) and pelvic examination is still common among obstetricians and gynecologists. 39 Studies examining women's attitudes and beliefs regarding routine pelvic examination showed that one-half of the women 21 years or older did not know the purpose of the pelvic examination, and yet most women believed that routine pelvic examinations were necessary for STI screening, contraception initiation, and cancer detection and have value in reassuring the patient that she is in good health, particularly among older women. 40,41 After education on the American College of Physicians' recommendation advising against routine pelvic examinations, substantially fewer women wanted to have one.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest a lag in clinical practice following the recommendations and guidelines. For example, the notion linking access to hormonal contraception (other than an IUD) and pelvic examination is still common among obstetricians and gynecologists …”
Section: Discussionmentioning
confidence: 99%
“…27 Despite these guidelines, many physicians continue to perform unnecessary pelvic examinations, especially in younger populations. 7,28,29 Many young women with history of IPV may be avoiding preventive clinic visits because they are worried that the visit may include a pelvic examination. This could be one potential reason for the decline in adequate cervical cancer screening over the past two decades.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] Despite these recommendations, many providers still require a pelvic examination prior to prescribing or administering contraception, creating an unnecessary barrier to access contraception, especially in vulnerable populations. 6,7 Intimate partner violence (IPV) affects millions of people in the United States (U.S.) and is a preventable and serious public health problem. IPV is defined by the CDC as abuse or aggression that occurs in close relationships and can include physical, sexual, or verbal abuse.…”
Section: Introductionmentioning
confidence: 99%